Adakah Hubungan antara Usia dan Gangguan Indera Perasa pada Pasien COVID-19? - Khalimatus Suanti; Fransiska, Fransiska; Astrid Pratidina Susilo (Keluwih: Jurnal Kesehatan dan Kedokteran, 2024)
Abstract—COVID-19 (coronavirus disease 2019) is a respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The clinical symptoms of COVID-19 patients vary widely, for example the olfactory and taste disorder. Several studies reported the prevalence of taste disorder of 71% to 88.8% in COVID-19 patient. This research aimed to determine the association between age and taste disorders during the spread of the Delta variant of COVID-19. A cross sectional study conducted on 42 subjects. The data was analyzed using Independent T-test. Statistical analyzed showed that 27 out of 42 subjects experienced taste disorders. The mean age of COVID-19 patients with taste disorders was 50 years (SD 12.83). In the independent T-test, a p-value of 0.613 was obtained (p>0.05), which means that there was no association between age and taste disorders. Taste disorders are caused by hyposalivation which begins to occur at the age of 65 and over. This study concluded no significant correlation between age and taste disorders in COVID-19 patients. Keywords: COVID-19 patients, age, taste disorders Abstrak—COVID-19 (coronavirus disease 2019) adalah penyakit pernapasan yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Gejala klinis pasien COVID-19 sangat bervariasi, di antaranya gangguan indera penghidu dan perasa. Beberapa penelitian melaporkan prevalensi gangguan indera perasa sebesar 71% hingga 88,8% pada pasien COVID-19. Penelitian ini bertujuan untuk mengetahui hubungan rerata usia dengan gangguan indera perasa selama penyebaran COVID-19 varian Delta. Studi cross sectional dilakukan pada 42 subjek penelitian. Teknik pengambilan data adalah total sampling, yaitu pada pasien yang rawat inap karena COVID-19. Data dianalisis dengan menggunakan Uji T-tidak berpasangan. Analisis statistik menunjukkan bahwa 27 dari 42 pasien mengalami gangguan indera perasa. Usia rata-rata pasien COVID-19 dengan gangguan indera perasa adalah 50 tahun (SD 12,83). Pada uji T-tidak berpasangan didapatkan nilai p sebesar 0,613 (p>0,05), yang berarti tidak ada hubungan antara usia dengan gangguan indera perasa. Kata kunci: pasien COVID-19, usia, gangguan perasa